1986
DOI: 10.1146/annurev.nu.06.070186.001103
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Microflora in Mammalian Nutrition

Abstract: A mammal is a complex organism consisting of eukaryotic animal cells and eukaryotic and prokaryotic microbial cells. Most of the microorganisms reside in communities in the gastrointestinal tract. These gastrointestinal microfloras are known to serve nutritional functions in ruminants, pseudoruminants, and monogastric mammals with only modest or no foregut fermentations but with extensive hindgut fermentations in blind cecal pouches. In adult animals, the microflora hydrolyzes exogenous (dietary) and endogenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
0
6

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(99 citation statements)
references
References 54 publications
1
92
0
6
Order By: Relevance
“…Until recently, bacteria content and activity proximal to the large intestine of the pig had been considered to be of little importance in nutritional terms (Hungate, 1984;Savage, 1986). Hovewer, the iclusion of subtherapeutic levels of antibiotics in diets has been shown to improve growth performance (Yen et al, 1987) and reduce intestinal bacterial ammonia production (Yen et al, 1990) in swine.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, bacteria content and activity proximal to the large intestine of the pig had been considered to be of little importance in nutritional terms (Hungate, 1984;Savage, 1986). Hovewer, the iclusion of subtherapeutic levels of antibiotics in diets has been shown to improve growth performance (Yen et al, 1987) and reduce intestinal bacterial ammonia production (Yen et al, 1990) in swine.…”
Section: Introductionmentioning
confidence: 99%
“…These gnotobiotic models have revealed that the microbiota facilitates the breakdown of otherwise indigestible polysaccharide components of our diet (4,5), regulates storage of calories extracted from the diet in adipocytes (3), metabolizes xenobiotics, including carcinogens (6, 7), modulates intestinal epithelial cell turnover (8)(9)(10)(11), and educates the immune system (12,13). The microbiota also collaborates with the host to regulate a number of aspects of postnatal gut development, including the assembly of the extensive network of capillaries in the mesenchymal cores of mouse small intestinal villi (14).…”
mentioning
confidence: 99%
“…This strongly suggests that lactobacilli may use mechanisms similar to those of pathogenic bacteria when colonizing mucosal surfaces. It is postulated that lactobacilli can adhere because of the presence of surface structures containing teichoic and lipoteichic acids linked to the cell wall peptidoglycan (15). Protein structures resembling the fuzzy layer extruding from the cell wall surfaces were also found.…”
Section: Discussionmentioning
confidence: 99%